Internet connectivity disruption in Iraq (Iraq) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Iraq. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: IQ-2026-0094. Severity: critical. Confidence: 67%